Paleoelevation estimates for the northern and central proto–Basin and Range from carbonate clumped isotope thermometry. Issue 3 (30th May 2013) - Lechler, Alex R.; Niemi, Nathan A.; Hren, Michael T.; Lohmann, Kyger C.
<x xml:space="preserve">Abstract</x> [1] Quantitative paleoelevation histories can help explain both why and how widespread Cenozoic extension occurred in the Basin and Range Province of western North America. We present new estimates of preextensional paleoelevations for the northern and central Basin and Range using clumped isotope (Δ47) thermometry of lacustrine carbonates collected from each region. Comparison of carbonate Δ47‐derived mean annual air temperature (MAAT) estimates ( 16°C–20°C) for the Late Cretaceous–Eocene Sheep Pass basin of east central Nevada with published MAAT estimates for the Eocene, coastal northern Sierra Nevada ( 20°C–25°C), suggests that the early Paleogene Sheep Pass basin had a paleoelevation of ≤2 km. Such a modest paleoelevation suggests that either (1) the proto–northern Basin and Range did not attain maximum paleoelevations of 3–4 km until the late Eocene–early Oligocene; or (2) the Sheep Pass basin was a local, high‐relief (>1 km) setting contained within a >3 km orogenic highland ("Nevadaplano"). Similarity of Δ47‐derived MAAT estimates ( 17°C–24°C) for carbonates from the central Basin and Range and the near–sea level southern Sierra Nevada Bena basin indicate that middle Miocene paleoelevations in the Death Valley region were ≤1.5 km. These fairly low paleoelevations are incompatible with preextensional crustal thicknesses >52 km and indicate that mean elevation change was minor (≤500 m) and lithospheric mass was not conserved during >100% Neogene extension of the central Basin and Range, but was instead likely compensated by synextensional magmatic additions to the crust.